2020
DOI: 10.3847/1538-3881/ab68df
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Massive Open Cluster NGC 1817 from K2: A Rich Population of Asteroseismic Red Clump, Eclipsing Binary, and Main-sequence Pulsating Stars

Abstract: We present a survey of variable stars detected in K2 Campaign 13 within the massive intermediate age (∼ 1 Gyr) open cluster NGC 1817. We identify a complete sample of 44 red clump stars in the cluster, and have measured asteroseismic quantities (ν max and/or ∆ν) for 29 of them. Five stars showed suppressed dipole modes, and the occurrence rates indicate that mode suppression is unaffected by evolution through core helium burning. A subset of the giants in NGC 1817 (and in the similarly aged cluster NGC 6811) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 84 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, star 765ʼs membership may also be in question due to it is relatively low parallax (Table 2), but its proper motions are consistent with NGC 7789 membership. The dereddened CMD presented in Figure of Sandquist et al (2020) for multiple open clusters shows that the approximate red clump center is at…”
Section: The Stellar Samplementioning
confidence: 98%
“…Furthermore, star 765ʼs membership may also be in question due to it is relatively low parallax (Table 2), but its proper motions are consistent with NGC 7789 membership. The dereddened CMD presented in Figure of Sandquist et al (2020) for multiple open clusters shows that the approximate red clump center is at…”
Section: The Stellar Samplementioning
confidence: 98%
“…Open clusters are known to host a rich variety of variable stars (Xue et al 2019;Joshi et al 2020a;Sandquist et al 2020). These stars play a crucial role in our understanding of stars' intrinsic properties such as pulsation, rotation, and emission.…”
Section: Introductionmentioning
confidence: 99%
“…Asteroseismology of solar-like oscillators is a strong tool for further improving such studies (e.g. Miglio et al 2012Miglio et al , 2016Handberg et al 2017;Arentoft et al 2019;Sandquist et al 2020;Tailo et al 2022;Howell et al 2022), however, it requires long and uninterrupted high-precision observations. This currently limits detailed asteroseismic cluster studies to those observed by CoRoT (Baglin et al 2006), Kepler (Borucki et al 2010) or K2 (Howell et al 2014), with a few exceptions (e.g.…”
Section: Introductionmentioning
confidence: 99%